Strongyloidiasis in Bornean Orangutan: A Case Report - Suandhika, Putu; Susanti, Agatha Ria; Sriningsih, Agnes Pratamiutami; Hina, Carlo Yunior Ray; Yanuartono, Yanuartono; Indarjulianto, Soedarmanto; Priyowidodo, Dwi (Universitas Airlangga, 2023)
This study reported the diagnosis and treatment of Strongyloidiasis in two Bornean orangutans (Pongo pygmaeus); adult male aged 23 years, weighing 100 kg and an infant female orangutan, 4 years old, weighing 13,6 kg. Samples were physically and laboratory examined for faeces using the Mini-FLOTAC method. Therapy was performed on the adult orangutan using albendazole at a dose of 400 mg individual twice a day for 4 days, orally. The infant orangutan was administered albendazole at a dose of 10 mg/kg BW once a day for 3 days orally. From several physical examinations, both orangutans looked active, body temperature and oral mucosa color were normal, green feces with solid consistency in the adult orangutan and brown with solid consistency in the infant orangutan. Microscopic faeces examination of the adult orangutan showed Strongyloides sp. as many as 1005 eggs per gram (EPG) of feces, and the infant orangutan as many as 2490 larvae per gram of feces. Both orangutans were diagnosed with severe Strongyloidiasis based on those examinations. Three days after starting treatment, the adult orangutan's EPG decreased to 890, and a week later, no Strongyloides sp. eggs or larvae were discovered. A week following treatment, no Strongyloides sp. was discovered in an infant orangutan. In conclusion, albendazole was an effective treatment for severe Strongyloidiasis in adult and infant orangutans. Strongyloidiasis can be a threat to both infant and adult orangutans without distinct clinical symptoms.